1995
DOI: 10.2118/25370-pa
|View full text |Cite
|
Sign up to set email alerts
|

Helical Buckling and Lock-Up Conditions for Coiled Tubing in Curved Wells

Abstract: An improved formula for critical buckling forces has been derived. This formula, which takes the well curvature into account, has been verified in small scale laboratory tests. The theory has been applied to survey data from a real horizontal well and it predicts that the well curvature substantially affects the critical force for helical buckling, and thereby also the maximum run-in length of coiled tubing. Criteria for operational limits, such as lock-up and tubing failure, are also discussed in the paper. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(37 citation statements)
references
References 8 publications
0
37
0
Order By: Relevance
“…He derived an improved formula for critical buckling forces, which takes the well curvature into account. The model predicts that the well curvature substantially affects the critical force for helical buckling [15]. Mitchell presented the large-displacement analysis of a helically buckled slender beam and predicted that shear force and twisting moment are induced in helically buckled pipe without externally applied torque [16].…”
Section: Introductionmentioning
confidence: 99%
“…He derived an improved formula for critical buckling forces, which takes the well curvature into account. The model predicts that the well curvature substantially affects the critical force for helical buckling [15]. Mitchell presented the large-displacement analysis of a helically buckled slender beam and predicted that shear force and twisting moment are induced in helically buckled pipe without externally applied torque [16].…”
Section: Introductionmentioning
confidence: 99%
“…The compressive force required for the string to transition from a sine wave to helix is 41% more than the force necessary for it to initially buckle into a sine wave (9). The force required to reach the locking point in a straight well is always higher than the force required for helical buckling.…”
Section: Model Assumption Validationsmentioning
confidence: 99%
“…Specifically, Eqs. 1 and 2 were derived by He and Kyllingstad to predict the normal contact forces between the drill string and the well wall (9).…”
Section: Analytical Model For Predicting Engagement/disengagement Of mentioning
confidence: 99%
“…μ is the kinematic viscosity of liquid (Pa.s), Dci is the outside diameter of sucker rod coupling (m), Dti is the outside diameter of tube (m), Dri is the element diameter of SRS (m). For the researches on the deformation of helical buckling for SRS, Lubinski, Xiaojun, Mitchell and Guohua give theoretical analysis method and experiment [11][12][13]. And the damping coefficient is derived by Shimin, and the equation is expressed [2].…”
Section: Dynamic Model and Nonlinear Second-order Differential Equationsmentioning
confidence: 99%
“…Therefore, the research on deformation of helical buckling for SRS is reported in Refs. [11][12][13] and need not be repeated here.…”
Section: Dynamic Model and Nonlinear Second-order Differential Equationsmentioning
confidence: 99%